2010
DOI: 10.1097/wno.0b013e3181ce18eb
|View full text |Cite
|
Sign up to set email alerts
|

MRI Demonstrates Restricted Diffusion in Distal Optic Nerve in Atypical Optic Neuritis

Abstract: A 4-year-old healthy girl with acute visual loss in the right eye had ophthalmoscopic evidence of a swollen optic disc combined with central retinal artery and vein occlusion in the affected eye. MRI showed that the intraorbital optic nerve on the affected side was thickened and enhancing. Diffusion-weighted imaging showed restricted diffusion in the distal intraorbital segment of the optic nerve, consistent with infarction attributed to compression or inflammation of the vessels serving the optic nerve and re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…12,14,16 Restricted diffusion on DWI within the optic nerves has also been shown to be associated with acute inflammatory disorders such as lymphomatous optic neuropathy 17 and optic neuritis. 18 The frequency of restricted diffusion in optic neuritis is not clear; however, one retrospective study found that 8% of patients with clinical optic neuritis showed restricted diffusion on DWI. 19,20 Furthermore, changes within the optic nerve are more commonly seen with gadolinium enhanced imaging, 20 a feature not usually associated with acute ischaemic lesions.…”
Section: Discussion and Literature Reviewmentioning
confidence: 99%
“…12,14,16 Restricted diffusion on DWI within the optic nerves has also been shown to be associated with acute inflammatory disorders such as lymphomatous optic neuropathy 17 and optic neuritis. 18 The frequency of restricted diffusion in optic neuritis is not clear; however, one retrospective study found that 8% of patients with clinical optic neuritis showed restricted diffusion on DWI. 19,20 Furthermore, changes within the optic nerve are more commonly seen with gadolinium enhanced imaging, 20 a feature not usually associated with acute ischaemic lesions.…”
Section: Discussion and Literature Reviewmentioning
confidence: 99%
“…Restricted diffusion within the optic nerve was initially demonstrated in peri-operative PION[ 3 ] and subsequently in mucormycosis,[ 4 ] cavernous sinus thrombophlebitis,[ 5 ] thrombocytosis[ 6 ] and optic peri-neuritis. [ 7 ] Similar imaging findings in a case of lymphoma were attributed to hypercellularity due to tumor rather than infarction. [ 8 ] Infarction of the retina as well as the optic nerve has also been demonstrated in mucormycosis.…”
mentioning
confidence: 88%
“…Several case reports have described diffusion restriction along the ON as a marker of infarction in ischemic optic neuritis, [14][15][16][17][18][19] with other studies mentioning ON diffusion restriction in the setting of infection, idiopathic orbital inflammatory syndrome, cellulitis, and orbital lymphoid lesions. 9,20,21 Although these reports describe the signal characteristics along the length of the ON, we have mainly focused on the appearance of the ON head (Figs 1 and 2).…”
Section: Discussionmentioning
confidence: 99%